RESPUESTA BIOLOGICA EN JUVENILES DE LANGOSTA DE AGUA DULCE (Cherax quadricarinatus) ALIMENTADOS CON SELENIO EN DIETA - Menéndez Castro, Marlon Moisés (2023)
The feeding and nutrition of young lobsters are key factors to increase the growth and survival of these species, which the objective of this study was to evaluate the effect of growth in juveniles with selenium in the diet on the freshwater lobster (Cherax quadricarinatus). factors on biological parameters, development, nutrition and survival in freshwater lobster juveniles (c. quadricarinatus).